PERAN GURU DALAM MEMBANGUN MINAT MENGHAFAL AL QUR’AN PADA MASA PANDEMI DI MIT SAHABAT QUR’AN IBNU MAS’UD GODEAN SLEMAN YOGYAKARTA - Nabila Nurul Amalia; Fu’ad Arif Noor (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This research was conducted during the covid-19 pandemic, that students' interest in learning and memorizing was very low, mainly influenced by learning carried out with the online system (online) making students bored and bored more quickly with a monotonous learning system. The goal is to find out how big a teacher's role is in building students' interest in memorizing the Qur'an during a pandemic. The research method uses a qualitative descriptive approach, data collection techniques with observation, interviews and documentation techniques. The research subjects were tahfidz teachers and 20 grade 2 students at MIT Sahabat Qur'an Ibnu Mas'ud Yogyakarta. The results of the research are that: The role of the teacher in building interest in memorizing the Qur'an during the pandemic is: tahfidz teachers always provide motivation and support to their students such as praise, advice with an individual chat approach via telephone, tahfidz teachers still give memorization tasks to students to memorized at home according to a predetermined target, and the teacher does whatever is best as a facilitator to support the spirit of memorizing at home by sending children's memorization targets. The obstacles experienced by teachers when building interest in memorizing the Qur'an during the pandemic are: There are students who have not been able to read the Qur'an well, limited interaction between teachers and students, and an environment that is not conducive.